Transcytosis of Bacillus subtilis extracellular vesicles through an in vitro intestinal epithelial cell model - Domínguez Rubio, Ana Paula (2020)
Bacterial EVs have been related to inter-kingdom communication between probiotic/pathogenic bacteria and their hosts. Our aim was to investigate the transcytosis process of B. subtilis EVs using an in vitro intestinal epithelial cell model. In this study, using Confocal Laser Scanning Microscopy, we report that uptake and internalization of CFSE-labeled B. subtilis EVs (115 nm ± 27 nm) by Caco-2 cells are time-dependent. To study the transcytosis process we used a transwell system and EVs were quantified in the lower chamber by Fluorescence and Nanoparticle Tracking Analysis measurements. Intact EVs are transported across a polarized cell monolayer at 60–120 min and increased after 240 min with an estimated average uptake efficiency of 30% and this process is dose-dependent. EVs movement into intestinal epithelial cells was mainly through Z axis and scarcely on X and Y axis. This work demonstrates that EVs could be transported across the gastrointestinal epithelium. We speculate this mechanism could be the first step allowing EVs to reach the bloodstream for further delivery up to extraintestinal tissues and organs. The expression and further encapsulation of bioactive molecules into natural nanoparticles produced by probiotic bacteria could have practical implications in food, nutraceuticals and clinical therapies.